2022
DOI: 10.1159/000526688
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications of Microscopic Fenestration for Middle Fossa Arachnoid Cysts: A Retrospective Study of 38 Cases and Literature Review

Abstract: Introduction: Middle fossa arachnoid cyst (MFAC) is one of the most common cranial cysts in children, and the various postoperative complications following cyst fenestration represent a major concern. We conducted a retrospective study in our department and performed a systematic review of the literature to identify the risk factors for complications. Methods: A retrospective survey was conducted on 38 patients with MFAC (< 14 years) who underwent microscopic fenestration from January 2019 to December 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In the multivariate analysis, only postoperative hydrocephalus was significant ( p = 0.02). Complications and frequencies after both microscopic/endoscopic and stereotactic procedures in the adult group of our cohort were comparable to other studies [ 2 , 8 , 18 , 21 ]. In the pediatric cohort, we have to emphasize a high risk of intraoperative bleeding due to altered anatomical structures, which was also described earlier [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the multivariate analysis, only postoperative hydrocephalus was significant ( p = 0.02). Complications and frequencies after both microscopic/endoscopic and stereotactic procedures in the adult group of our cohort were comparable to other studies [ 2 , 8 , 18 , 21 ]. In the pediatric cohort, we have to emphasize a high risk of intraoperative bleeding due to altered anatomical structures, which was also described earlier [ 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…In the pediatric cohort, we have to emphasize a high risk of intraoperative bleeding due to altered anatomical structures, which was also described earlier [ 25 ]. One study [ 18 ] defined a postoperative subdural hematoma as a possible risk factor favoring revision surgery; however, we were the first to describe postoperative hydrocephalus as a significant finding for re-surgery.…”
Section: Discussionmentioning
confidence: 94%
“… 8 Various treatment methods for symptomatic arachnoid cysts have been described, including craniotomy for cyst drainage and/or resection, 6 , 8 , 9 as well as microsurgical or endoscopic cyst fenestration. 3 , 18 , 19 Previous prospective studies have found that surgery for arachnoid cyst treatment is relatively safe and can yield significant clinical benefit in both children and adults. 1 , 20 Cystoperitoneal shunting is another surgical option for these patients and has been described in prior cases of symptomatic arachnoid cysts.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Additionally, complications associated with cyst fenestration such as subdural hygroma and cyst recurrence are avoided with shunt placement. 19 , 22 However, permanent shunts and accompanying craniotomies have their own set of potential complications and risks, such as shunt revision and infection, and should also be taken into account during treatment selection.…”
Section: Discussionmentioning
confidence: 99%